Hepatoprotective potential of a novel quinazoline derivative in thioacetamide-induced liver toxicity - Salama, Suzy; Kue, Chin Siang; Mohamad, Haryanti; Omer, Fatima; Ibrahim, Mohamed Yousif; Abdulla, Mahmood; Ali, Hapipah; Mariod, Abdalbasit; Jayash, Soher Nagi (Frontiers in Pharmacology, 2022)
Purpose: The compound quinazoline (Q-Br, 3-(5-Bromo-2-hydroxybenzylideneamino)-2-(5-bromo-2 hy-droxyphenyl) 2,3-dihydroquinazoline-4(1H)-one (Q-Br) was evaluated for its antioxidant capacity, and po-tential hepatoprotectivity against sub-chronic liver toxicity induced by thioacetamide in rats. Materials and Methods: Rats were assigned into 5 groups including healthy (normal) and cirrhosis control groups were orally given 5% Tween 20, reference control group was given Silymarin dose of 50 mg/kg, low dose Q-Br dose and high dose Q-Br groups were given daily dose of 25 mg/kg and 50 mg/g Q-Br re-spectively. Liver status was detected via fluorescence imaging with intravenous injection of indocyanine green (ICG) and plasma ICG clearance test. Liver malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were also tested. The degree of fibrosis was deter-mined histologically by haematoxylin and eosin, and Masson’s Trichrome staining. The immunohisto-chemistry of liver tissue inhibitor of metalloproteinase (TIMP-1), matrix metalloproteinase (MMP-2) and alpha-smooth muscle actin (α-SMA) were performed. Results: Q-Br recorded mild antioxidant capacity, dose-dependent improvement in the liver status and in-hibition of oxidative stress compared to cirrhosis control. Histopathology notified remarkable reduction in the degree of fibrosis. Immunohistochemistry revealed obvious low expression of MMP-2 and α-SMA along with higher expression of TIMP-1 in Q-Br and Silymarin-treated livers. Conclusions: Q-Br treatment altered the course of toxicity induced by thioacetamide suggesting significant hepatoprotective potential of Q-Br treatment.